2020
DOI: 10.1177/0363546520908805
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anterolateral Ligament Healing After Anatomic Anterior Cruciate Ligament Reconstruction

Abstract: Background: Few studies have reported the healing process of anterolateral ligament (ALL) injuries. Purpose/Hypothesis: This study investigated the healing status of ALL injuries after primary anterior cruciate ligament (ACL) reconstruction (ACLR). Additionally, we investigated the association between the healing status of ALL injuries and associated lesions such as osseous lesions and meniscal tears occurring at the time of an ACL rupture. We hypothesized that acute ALL injuries show a high rate (more than tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 59 publications
2
17
0
2
Order By: Relevance
“…Although direct comparison between studies is precluded by important methodological differences (imaging protocols, classification systems, and the inclusion of chronic as well as acute injuries in the current study), the overall healing rates are broadly similar across studies (current study, 30.3%; Lee et al, 23 30%). It is also of interest to note similar findings with regard to the limited ability of complete injuries to fully heal (current study, 6 complete injuries, full healing rate 0%; Lee et al, 23 16 complete injuries, 12 remained discontinuous, 3 nonvisualized [assumed complete injuries], full healing rate 1/16; 6.25%). Although the multivariate analysis in the current study did not demonstrate a difference in the rate of full healing between grade B and grade C injuries at 12 months (37% vs 0%; OR, 0.132; 95% CI, 0.01-3.22; P = .2141), the trend across both studies of a lower healing rate in complete injuries warrants additional future investigation with a larger sample size.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although direct comparison between studies is precluded by important methodological differences (imaging protocols, classification systems, and the inclusion of chronic as well as acute injuries in the current study), the overall healing rates are broadly similar across studies (current study, 30.3%; Lee et al, 23 30%). It is also of interest to note similar findings with regard to the limited ability of complete injuries to fully heal (current study, 6 complete injuries, full healing rate 0%; Lee et al, 23 16 complete injuries, 12 remained discontinuous, 3 nonvisualized [assumed complete injuries], full healing rate 1/16; 6.25%). Although the multivariate analysis in the current study did not demonstrate a difference in the rate of full healing between grade B and grade C injuries at 12 months (37% vs 0%; OR, 0.132; 95% CI, 0.01-3.22; P = .2141), the trend across both studies of a lower healing rate in complete injuries warrants additional future investigation with a larger sample size.…”
Section: Discussionsupporting
confidence: 79%
“…To our knowledge, no previous prospective serial MRI study has evaluated the rate and duration of the healing process of ALL injuries. However, in a recent retrospective study, Lee et al 23 reported that approximately 30% of patients demonstrated good healing (defined as taut, linear, and low signal intensity) of the ALL based on MRI at 12 months after acute (within 1 month of injury) ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…8,15,27,28,32,35 The healing potential of the ALL is not well-known. Lee et al 23 evaluated this parameter and found poor healing in approximately 70% of the patients after 1 year. This nonhealing scenario is important because biomechanical studies have suggested that in cases of an acute combined injury of the ACL and the anterolateral structures, isolated reconstruction of the ACL does not reestablish normal knee biomechanics.…”
mentioning
confidence: 99%
“…As previous literature demonstrated improved clinical outcome after ALL reconstruction [ 9 , 10 , 13 ], the clinical relevance of partial ALL ruptures or strains is of high interest to define more detailed criteria for a simultaneous ALL reconstruction in the future. Moreover, the healing potential of the ALL is low and a rotatory laxity most likely will persist if treated non-operatively [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%